1967
DOI: 10.1590/s0006-87051967000100030
|View full text |Cite
|
Sign up to set email alerts
|

Absorção de nutrientes pela cultura do feijoeiro

Abstract: SINOPSEFoi determinada a marcha de absorção dos macronutrientes essenciais pela cultura do feijoeiro (Phaseolus vulgaris L.) em casa de vegetação. O máximo de crescimento foi atingido ao completar a planta 50 dias de idade. Os elementos N, K e Ca foram absorvidos até aos 50 dias da germinação. O Mg e S, até aos 70 e 60 dias, respectivamente. O fósforo foi absorvido durante todo o ciclo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
16
1
17

Year Published

1990
1990
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 1 publication
8
16
1
17
Order By: Relevance
“…Day after emergence required in high amounts (Gallo & Miyasaka 1961;Haag et al, 1967). Regardless of the treatment, it was observed that N, K and Ca were the nutrients accumulated in larger amounts in the stem, which was similar to results obtained by Gallo & Miyasaka (1961) and Cobra Netto et al (1971) in studies with common bean.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Day after emergence required in high amounts (Gallo & Miyasaka 1961;Haag et al, 1967). Regardless of the treatment, it was observed that N, K and Ca were the nutrients accumulated in larger amounts in the stem, which was similar to results obtained by Gallo & Miyasaka (1961) and Cobra Netto et al (1971) in studies with common bean.…”
Section: Resultssupporting
confidence: 87%
“…According to Brito et al (2009), the largest proportion of N absorbed by common bean (around 80 %) was derived by symbiotic fixation, and the highest rate of N symbiotic fixation occurred at the pre-flowering stage. Haag et al (1967) found that Mg was absorbed up to 70 DAE, i.e., a similar period as observed in this study (Figure 6d). The amount of Ca accumulated in the shoot increased up to 70 DAE, different from results obtained by Haag et al (1967) andCobra Netto et al (1971), who observed Ca absorption by common bean up to 50 and 55 DAE, respectively.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations